Double-balloon cervical ripening catheter works well as an intrauterine balloon tamponade in post-abortion massive hemorrhage - Kuan-Hao Tsui; Li-Te Lin; Ken-Jen Yu; Shun-Fen Chen; Wen-Hsun Chang; Shu Yu; Jiin-Tsuey Cheng; Peng-Hui Wang (Elsevier, 2012)
Objective: Clinical experience in the management of post-abortion hemorrhage is limited. Case Reports: Two women with severe post-abortion hemorrhage were reported. One case occurred after methotrexate treatment of Cesarean scar pregnancy and the other occurred after abortion surgery. Both patients were successfully treated with a double-balloon cervical ripening catheter inducing intrauterine balloon tamponade. Conclusion: Use of a double-balloon cervical ripening catheter either before or after systemic methotrexate treatment is one of the choices in the management of severe post-abortion hemorrhage and can prevent the use of more invasive and/or destructive procedures.